BACTERIOLOGICAL COMPARISON OF COCKLES FROM THREE PRODUCING AREAS IN PENINSULAR MALAYSIA - Fisal Ahmad; Noryati Ismail; Hamdan Jaafar; Wan Norhana Nordin (Tropical Life Sciences Research, 2007)
Kuala Sg. Jarum Mas, Kuala Sepetang, the river estuaries in the state of Perak and Kuala Juru in Penang have been identified as major cockle producing areas under the Balance of Trade (BOT) program for mollusc. Since the bacteriological assessment of cockles from Kuala Sepetang and Kuala Sg. Jarum Mas has not been carried out before, this study was initiated to compare the bacteriological quality of cockles from these areas as compared to the extensively studied area, Kuala Juru. Cockles were collected in February, April and June 2004 and examined for Standard Plate Count (SPC), total coliform (TC), fecal coliform (FC) counts, Escherichia coli (EC) counts and presence of pathogens (Salmonella spp., Vibrio cholerae and Vibrio parahaemolyticus). Sample collection and analyses were carried out according to standard microbiological methods. The results indicated that cockles from Kuala Juru and Kuala Sepetang exceeded the safety level for SPC (5 × 105 CFU/g), FC (< 300 MPN/100 g) and EC counts (< 230 MPN/100 g) while, result from Kuala Sg. Jarum Mas falls below the safety level for the same parameter. Statistical analyses showed significant difference for the three areas (p < 0.05) for SPC. Meanwhile significant differences were observed in TC, FC and EC counts between Kuala Juru with Kuala Sepetang and Kuala Sg. Jarum Mas (p < 0.05). Vibrio parahaemolyticus was present in samples from all locations examined, whereas cholerae was only detected in cockles from Kuala Juru in February. Presence of Salmonella in samples from Kuala Juru and Kuala Sepetang showed that it does not comply with the safety recommendations. The results from this study strongly recommend that cockles harvested in Kuala Juru and Kuala Sepetang to undergo decontamination before sale and eventual consumption. Kuala Sg. Jarum Mas, Kuala Sepetang, muara sungai di Perak dan Kuala Juru di Pulau Pinang telah dikenal pasti sebagai kawasan utama penghasilan kerang dibawah program Perseimbangan Dagangan (BOT) bagi kerang-kerangan. Oleh sebab penilaian bakteriologi terhadap kerang dari Kuala Sepetang dan Kuala Sg. Jarum Mas belum pernah dijalankan, kajian ini dimulakan bagi membuat perbandingan antara kualiti bakteriologi dari kawasan ini dengan kerang dari Kuala Juru yang telah banyak dikaji. Kerang telah dipungut pada bulan Februari, April dan Jun 2004 dan diuji bagi hitungan plat standard (SPC), koliform total (TC), koliform najis (FC), Escherichia coli (EC) dan kehadiran patogen (Salmonella spp., Vibrio cholerae dan Vibrio paraheamolyticus). Pengambilan sampel dan analisis telah dijalankan menurut kaedah mikrobiologi standard. Keputusan menunjukkan bahawa kerang dari Kuala Juru dan Kuala Sepetang melebihi had keselamatan bagi SPC (5 × 105 CFU/g), FC (< 300 MPN/100 g) dan EC counts (< 230 MPN/100 g) sementara keputusan dari Kuala Sg. Jarum Mas adalah jauh rendah daripada had keselamatan bagi parameter yang sama. Analisis statistik menunjukkan perbezaan yang signifikan (p < 0.05) bagi SPC di ketiga-tiga buah kawasan. Sementara itu, perbezaan signifikan diperhatikan pada hitungan TC, FC dan EC antara Kuala Juru dengan Kuala Sepetang dan Kuala Sg. Jarum Mas (p < 0.05). Vibrio parahaemolyticus didapati hadir dalam sampel dari semua kawasan yang diuji manakala V. cholerae hanya terdapat dalam kerang dari Kuala Juru pada bulan Februari. Kehadiran Salmonella dalam sampel dari Kuala Juru dan Kuala Sepetang menunjukkan bahawa sample tersebut tidak memenuhi saranan had keselamatan. Keputusan kajian ini menyarankan agar kerang yang dipungut dari Kuala Juru dan Kuala Sepetang melalui dekontaminasi sebelum pemasaran dan penggunaan seterusnya.